Evaluation of Cerebral Infarction in Diabetic Patients With the history of Hypertension on Magnetic Resonance Imaging - R. Siddique, S. M. Yousaf Farooq, S. Z. Abidin, S. Qayyum, R. Shahzadi, S. Arif, M. Ali, A. Iqbal, Mahjabeen, M. Fatima, S. Aima Gilani (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mortality rate of individual in later age is increasing due to Cerebral infarction among the diabetic and hypertensive patients that leads towards the complexity within the patients. This study Considered to determine Cerebral Infarction in Diabetic patients with the history of hypertension on Magnetic Resonance Imaging. Aim: To Determine the Evaluation of Cerebral Infarction in Diabetic Patients with the history of Hypertension on MRI Duration of study: 01-May-2021 to 01- September-2021 Methodology: The study will be supervised in 162 Diabetic as well as Hypertensive patients comprising Genders for evaluation cerebral infarction through MRI. Results: In our study different groups of patients formed on the basis of their age and calculated the minimum and maximum age of the patients which are 41years and 91years respectively out of 162 patients. Also calculated the mean age as well as the value of standard deviation among the patients which is 67.35 and ±8.905 respectively. Different groups of patients also formed on the basis of their gender and also calculated their frequency 77 males and 85 females as well as percentages 47.5% males and 52.5% females. Based on data calculated the single infarction 27(16.7%) multiple infarction 48(29.6%) and also calculated the frequency and percentage of collectively patients appeared with the cerebral infarction 75(46.3%) and in which cerebral infarction absent 87(53.7%) out of 162 Patients. Conclusion: It is conducted a Survey on minute level and observed all the data related to cerebral infarction and concluded that the MRI is the good imaging device for the evaluation of Cerebral Infarction. It provides a pattern which ideal designate tried with likewise exploration as well as assessment upon a Larger population.